1981
DOI: 10.1111/j.1399-3054.1981.tb02722.x
|View full text |Cite
|
Sign up to set email alerts
|

Promotive effect of polyvinylpolypyrrolidone on pollen embryogenesis in Datura innoxia

Abstract: Pollen embryos of Datura innoxia Mill are produced in larger numbers from anthers on agar‐gelled medium containing polyvinylpolypyrrolidone than on control. The best response is observed with 0.5% polyvinylpolypyrrolidone. The effect is possibly due to adsorption of substances (phenolics) emanating from cultured anthers and inhibiting the development of pollen grains into embryos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The initial inhibition may be caused by adsorbtion of some conditioning substance, released by the anthers, as suggested by Johansson and Eriksson (1984). The stimulation of embryogenesis during the last weeks of incubation is probably caused by adsorbtion of phenolic substances, as suggested by Tyagi et al (1981). It is also worth observing that PVPP, bound in solid medium severely inhibited embryogenesis, both alone and especially in combination with AC.…”
Section: Discussionmentioning
confidence: 81%
“…The initial inhibition may be caused by adsorbtion of some conditioning substance, released by the anthers, as suggested by Johansson and Eriksson (1984). The stimulation of embryogenesis during the last weeks of incubation is probably caused by adsorbtion of phenolic substances, as suggested by Tyagi et al (1981). It is also worth observing that PVPP, bound in solid medium severely inhibited embryogenesis, both alone and especially in combination with AC.…”
Section: Discussionmentioning
confidence: 81%
“…Embryo production was improved by the addition of PVP in the culture medium that also decreased anther browning. Polyvinylpolypyrrolidone, an insoluble high molecular weight, cross-linked polymer of PVP, had a promotive effect on anther culture of Datura (Tyagi et al 1981) and browning has been shown as detrimental for embryogenesis in rubber tree callus (Housti. et al 1991).…”
Section: Resultsmentioning
confidence: 99%
“…According to these results, Zhong et al (1995) alleviated anther and medium browning in anther culture of sunflower by the addition of 0.1% PVP in culture medium. PVP is insoluble with high molecular weight and has also shown promotive effects on anther culture of Datura (Tyagi et al, 1981).…”
Section: Discussionmentioning
confidence: 99%